Modeling and Computational Analysis of Turbulent Free convection in Tall Enclosure Filled with Nano- Fluid - Amori, Karima E.; Hunehen, Qasim Kadhim (Basrah Journal for Engineering Sciences, 2014)
In this work, the turbulent buoyancy driven fluid flow and heat transfer in a differentially heated tall rectangular enclosure filled with nanofluid is quantified numerically. The two dimensional governing differential equations (continuity, momentum, energy and low Reynolds number LRN k-ω turbulence equations) are discretized using the finite volume method. SIMPLE algorithm is employed to obtain stabilized solution for high Rayleigh numbers. Two types of nanofluids namely, Al2O3-water and Cu-water, were considered. The effect of Rayleigh number (1010 to 1012), diameter of nanoparticles in the range 25-100 nm, nanoparticle volume fraction in range 0-0.08 and the aspect ratio (30, 40 and 50) on fluid flow and heat transfer are investigated. The present results are compared with previously published work and a qualitative agreement with good validation is obtained. Results show that addition of nanoparticles makes the liquid be more viscous which decreases the vertical velocity component and also decreases the temperature gradient near the walls. Also an announced heat transfer enhancement is obtained with nanoparticle volume fraction reaching a maximum point called optimal volume loading, at which the maximum convective heat transfer is obtained, and then it decreased with further increase of volume fraction.